Current trends in aflatoxin research - Baranyi, Nikolett (Acta Biologica Szegediensis, 2013)
Aflatoxins are decaketide-derived secondary metabolites which are produced by a complex biosynthetic pathway. Aflatoxins are among the economically most important mycotoxins. Aflatoxin B1 exhibits hepatocarcinogenic and hepatotoxic properties, and is frequently referred to as the most potent naturally occurring carcinogen. Acute aflatoxicosis epidemics occurred in several parts of Asia and Africa leading to deaths of several hundred people. Recent data indicate that aflatoxins are produced by 20 species assigned to three sections of the genus Aspergillus: sections Flavi, Nidulantes and Ochraceorosei. The economically most important producer is A. flavus and its relatives. Compounds with related structures include sterigmatocystin, an intermediate of aflatoxin biosynthesis produced by several Aspergilli and species assigned to other genera, and dothistromin produced by a range of non-Aspergillus species. Aflatoxin producers and consequently aflatoxin contamination occur frequently in various food products mainly in tropical and subtropical areas of the world. However, climate change led to the occurrence of aflatoxin producing species, especially A. flavus in areas where they were not prevalent previously. Molecular genetic and genomic studies led to the clarification of aflatoxin and sterigmatocystin biosynthetic pathways in a range of producing organisms, and provided insight into the metabolism and effect of aflatoxins. In this review, we wish to give an overview on recent progress of aflatoxin research including producing organisms, occurrence, biosynthesis and molecular detection of aflatoxins.